2018
DOI: 10.4194/1303-2712-v18_4_08
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Two experiments were conducted to investigate the effects on growth, survival and anti-inflammatory cytokine (Interleukin-10) using with Nannochloropsis concentration in diets of sea cucumber Apostichopus japonicus. In the first experiment, 60 days feeding trail was conducted to evaluate the growth performance and survival of the sea cucumber fed on six experimental diets containing different inclusion level of Nannochloropsis oculata (0%, 2%, 4%, 6%, 8%, 10%) in recirculating aquaculture system. Specific grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Naturally, gut contents of sea cucumber A. japonicus have lots of algae [12]. Arachidonic acid, eicosapentaenoic acid, the polyunsaturated fatty acids biomarker of sea weeds, Saccharina japonica, represents the higher mass fraction among polyunsaturated fatty acids in the body wall of sea cucumbers [31,32,33,34,2] which indicate that sea weeds, Saccharina japonica might have an excellent contribution to sea cucumber food source. The present study showed that specific growth rate (SGR) of sea cucumber A. japonicus fed with 15% Saccharina japonica containing diet was as high as those fed with D 0 (Control) diet (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Naturally, gut contents of sea cucumber A. japonicus have lots of algae [12]. Arachidonic acid, eicosapentaenoic acid, the polyunsaturated fatty acids biomarker of sea weeds, Saccharina japonica, represents the higher mass fraction among polyunsaturated fatty acids in the body wall of sea cucumbers [31,32,33,34,2] which indicate that sea weeds, Saccharina japonica might have an excellent contribution to sea cucumber food source. The present study showed that specific growth rate (SGR) of sea cucumber A. japonicus fed with 15% Saccharina japonica containing diet was as high as those fed with D 0 (Control) diet (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Sea cucumber Apostichopus japonicus belongs to Echinodermata, Holothuroidea, is a commercially important species in China, Japan and Republic of Korea [1,2]. Its market demand has increased with increasing interest as a healthy food for human.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations